Safety, Feasibility, and Efficacy of Transcutaneous Tibial Nerve Stimulation in Acute Spinal Cord Injury Neurogenic Bladder: A Randomized Control Pilot Trial - Stampas, Argyrios; Korupolu, Radha; Zhu, Liang; Smith, Christopher P.; Gustafson, Kenneth (Neuromodulation (Malden, Mass.), 2019)
Objectives We investigated whether transcutaneous tibial nerve stimulation (TTNS) in acute spinal cord injury was safe and feasible, and could achieve neuromodulation and improve cystometrogram parameters during acute inpatient rehabilitation. Materials and Methods Participants were consecutive acute traumatic spinal cord injury patients admitted for acute inpatient rehabilitation, randomized to a 2‐week trial of TTNS v sham stimulation. Primary outcomes were safety and feasibility of TTNS and secondary outcomes were bladder measures based on pre‐ and post‐TTNS cystometrogram by group and within groups, including bladder capacity, detrusor hyperreflexia, pressures, and detrusor‐sphincter dyssynergia, as well as filling sensations and desire to void. The principle investigator and subjects were blinded to treatment allocation. Results A total of 19 subjects consented to the study and completed the stimulation protocol. Morbidity was similar between groups and compliance was 100% to the TTNS protocol. Based on a lack of rehabilitation interruptions and comments from staff, TTNS was feasible. Post‐cystometrogram parameters were significant for lower volumes until sensation in the control group and prolonged volumes until sensation in the TTNS group. The control group had significant changes of increased detrusor‐sphincter dyssynergia and decreased bladder capacity. This was not significantly changed in the TTNS group. Conclusions TTNS is a safe and feasible modality that can be performed during inpatient rehabilitation of acute traumatic spinal cord injury. Bladder capacity and episodes of detrusor‐sphincter dyssynergia significantly worsened in the control group and did not significantly change in the TTNS group, suggesting that TTNS can alter the course of neurogenic bladder via neuromodulation.